IDENTIFIKASI GENUS BAKTERI ASAM LAKTAT DARI NIRA AREN TERFERMENTASI SPONTAN - Syahidah Bannan Qonita; Vonny Setiaries Johan; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Palm sap contain sugar and other nutritional components that are good for the growth of microorganism, one of which lactic acid bacteria (LAB). The purpose of this research was to isolate and identify lactic acid bacteria genus from fermented sap of Arenga pinnata. Lactid acid bacteria were isolate in MRS agar supplemented with CaCO3 0.2%. Identificatied morpholologically including Gram staining, shape cell observation, catalase test and gases production from glucose test. Fourteen isolates were able to produce clear zone in MRS agar which supplemented by CaCO3 0.2%. The identification results showed that the fourteen isolates were Gram positive, basil form and coccus form, catalase negative and 13 isolates belong to homofermentative and one isolate belong to heterofermentative. Further identify was then performed on the growth at different temperature (10°C, 37°C and 45°C), growth at different NaCl concentrations (4% and 6.5%) and growth at different pH (4.4 and 9.6) in 3 isolates suspected to have different characteristics. Further identify showed that all isolates can grow at temperature 10-45°C, salt concentration 0-6.5% and acid pH but can’t grow in alkaline pH. Suspected of LAB isolates were belong to genus Lactobacillus and Pediococcus. Keywords: Fermented palm sap, lactic acid bacteria, Lactobacillus, Pediococcus